Pengaruh Citra Merek, Kualitas Produk dan Harga terhadap Keputusan Pembelian Produk Hand and Body Lotion Vaseline (Studi Kasus pada Mahasiswa Universitas Samudra) - Dewi Rosa Indah; Iza Afalia; Zenitha Maulida (Jurnal Samudra Ekonomi dan Bisnis, 2020)
This study aims to determine the effect of brand image, product quality and price on purchasing decisions on Vaseline hand and body lotion products. The population is female students of University Samudra who use these products. Because the number is not known with certainty, a sample of 96 people was determined using the Cochran formula. Data analysis method used is multiple linear regression analysis. The results of the study concluded that partially, brand image, product quality and price had a positive and significant effect on purchasing decisions for Vaseline hand and body lotion products. In addition, the results of the study stated that the brand image, product quality and price simultaneously had a significant effect on purchasing decisions on the product.